2021
DOI: 10.1101/2021.02.01.429248
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemogenetic dissection of the primate prefronto-subcortical pathways for working memory and decision-making

Abstract: The primate prefrontal cortex (PFC) is situated at the core of higher brain functions by linking and cooperating with the caudate nucleus (CD) and mediodorsal thalamus (MD) via neural circuits. However, the distinctive roles of these prefronto-subcortical pathways remain elusive. Combining in vivo neuronal projection mapping with chemogenetic synaptic silencing, we reversibly dissected key pathways from PFC to the CD and MD individually in single monkeys. We found that silencing the bilateral PFC-MD projection… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…In contrast to the DREADD-expressing SI D2 , sensoryevoked activity of the SI foot sole region in the same hemisphere was not attenuated following DCZ administration, but rather unexpectedly augmented as compared to the vehicle control condition (Figure 5A, bottom middle). PET analysis revealed that DREADD expression could not be detected within the SI foot sole region even at a lower threshold, where the DREADD at the axon terminal of the SI D2 neurons was observed in other cortical and subcortical regions (Figure S5B) (Nagai et al, 2020;Oyama et al, 2021). This result was histologically confirmed as well (data not shown).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…In contrast to the DREADD-expressing SI D2 , sensoryevoked activity of the SI foot sole region in the same hemisphere was not attenuated following DCZ administration, but rather unexpectedly augmented as compared to the vehicle control condition (Figure 5A, bottom middle). PET analysis revealed that DREADD expression could not be detected within the SI foot sole region even at a lower threshold, where the DREADD at the axon terminal of the SI D2 neurons was observed in other cortical and subcortical regions (Figure S5B) (Nagai et al, 2020;Oyama et al, 2021). This result was histologically confirmed as well (data not shown).…”
Section: Resultssupporting
confidence: 53%
“…To estimate the expression level of transduced DREADD in vivo, the specific binding of [ 11 C]DCZ was calculated as regional binding potential relative to nondisplaceable radioligand (BP ND ) using PMOD with an original multilinear reference tissue model (MRTMo) (Nagai et al, 2020). Since the signal in the BP ND image of [ 11 C]DCZ reflects both DREADD expression and background tracer binding (i.e., noise) (Yan et al, 2021), we removed the background noise by subtracting the BP ND value obtained with the control data of the same individual in which DREADD was not expressed (Oyama et al, 2021). The control data was obtained before AAV injection for monkey 2.…”
Section: In Vivo Pet Visualization Of Dreadd Expressionmentioning
confidence: 99%
“…We examined the behavioral effects of two oral DCZ doses (300 and 1,000 μg/kg) and an intramuscular DCZ dose (100 μg/kg) for comparison. Consistent with previous studies [17,21], intramuscular 100 μg/kg DCZ administration resulted in a delay-dependent decrease in the task performance for 1-2 h following administration (Fig. 3c).…”
Section: Oral Dcz Administration Selectively Induces Longer-lasting Behavioral Effects In Hm4di-expressing Monkeyssupporting
confidence: 92%
“…Three monkeys (#226, #229, and #245) were tested with a spatial delayed response task. The protocol was almost the same as of our previous study [21].…”
Section: Behavioral Taskmentioning
confidence: 99%
See 1 more Smart Citation